2007
DOI: 10.1375/twin.10.2.275
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Benefits of Vigorous Exercise: A Study of Discordant MZ Twin Pairs

Abstract: The physiological benefits of vigorous exercise are well established. The existence of psychological benefits is less clear, however, due to methodological limitations common to investigatory studies. Two of these limitations are the difficulty of establishing appropriate control groups and the large variety of highly specific measures of psychological function available for consideration of effects. To address these limitations, we identified 63 pairs of monozygotic twins from the National Survey of Midlife D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
6
0
1
Order By: Relevance
“…Previous research has shown that exercising has positive consequences for mood and general well-being, an effect that may well generalize to subjective health [32]. Conversely, the effects of smoking and drinking on health may only become noticeable after a period of prolonged exposure, and the 2-year interval employed in the present study may have been too short for detecting such effects [33].…”
Section: Discussionmentioning
confidence: 83%
“…Previous research has shown that exercising has positive consequences for mood and general well-being, an effect that may well generalize to subjective health [32]. Conversely, the effects of smoking and drinking on health may only become noticeable after a period of prolonged exposure, and the 2-year interval employed in the present study may have been too short for detecting such effects [33].…”
Section: Discussionmentioning
confidence: 83%
“…Although we cannot assess individual i after he or she has been exposed to a potential causal factor and after not having been exposed to the factor, we can treat a pair of MZ twins as being highly similar individuals who are nearly perfectly matched on many potential confounders (eg, gender, age, childhood environment, genetic code, etc.). Now, if Twin 1 has engaged in, say, regular physical exercise, whereas Twin 2 has not, our comparison of these two highly similar individuals on an outcome (subjective well-being) will help clarify the role regular physical exercise plays with regard to subjective well-being (24). Basic co-twin control designs of this nature are not perfect analogs of the counterfactual, of course, and they do not definitively demonstrate causation in and of themselves; however, these designs do approximate the comparison of the same person after exposure and nonexposure to a potential causal influence in a closer way than individual-level analysis (22).…”
Section: Co-twin Control Analysismentioning
confidence: 99%
“…Outros fatores relacionados ao sobrepeso e obesidade devem ser observados, como as longas jornadas de trabalho exercidas de maneira sentada, caracterizando comportamento sedentário 24 Há escassez na literatura de estudos de associação entre estresse e atividade física. Alguns mostram evidências de menores índices de estresse nos indivíduos que praticam atividades físicas [28][29][30] . Mas esse fato não é consenso.…”
Section: Discussionunclassified